An accessible hydrogeological tool to monitor critical groundwater resources in hard-rock aquifers - Rohde, Melissa M.; Edmunds, W. Mike; Sharma, Somendra (Frontiers in Environmental Science, 2015)
Groundwater resources are increasingly being relied on in rural areas for income generation and food security. However, there is currently a lack of simple, yet accessible hydrogeological tools to monitor critical groundwater resources, both for quantity and quality. This is particularly true in developing countries underlain by fractured hard rock aquifers, with low productivities. Electrical conductivity (EC) meters are presented here as an easy-to-use tool that can provide real-time data collection to enhance routine groundwater monitoring in rural areas. A program was established within a fractured hard rock watershed for over a year in Rajasthan, India to determine the effectiveness and controls over EC as a monitoring tool. The initial groundwater quality in this region was largely influenced by rainfall, modified by evapotranspiration with recognizable input from water-rock interaction in the later months following the monsoon season. Chloride concentrations were linearly correlated with EC in all of the sampled groundwater, but the strength of the correlation attenuated in the months following the monsoon. Recharge rates were estimated using the chloride mass balance (CMB) approach, and then compared to the recharge rates derived from using EC as a surrogate for in what is referred to here as the CMB-EC approach. Recharge rates estimated from the CMB and CMB-EC methods were statistically similar (p=0.44).